2008
DOI: 10.1016/j.jtcvs.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Lack of fludeoxyglucose F 18 uptake in posttreatment positron emission tomography as a significant predictor of survival after subsequent surgery in multimodality treatment for patients with locally advanced esophageal squamous cell carcinoma

Abstract: Posttreatment positron emission tomography with fludeoxyglucose F 18 reliably predicted histologic response and postoperative survival in advanced esophageal squamous cell carcinoma. This tool could potentially be used to tailor optimal treatment according to individual responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Furthermore, clinical over-staging may also lead to a reduced chance of cure in a number of patients, in which the diagnosis of T4 was made in error. Our previous studies 29) as well as recent reports 30) have shown that the metabolic response of esophageal cancers to preoperative CRT as assessed by FDG-PET more accurately reflects tumor regression and predicts prognosis, compared with that by conventional imaging including CT. Therefore, accurate initial staging and response evaluation by using multimodal diagnostic tools including FDG-PET is no doubt necessary to provide appropriate treatments and also to improve prognosis of esophageal cancer patients with T4 tumors.…”
Section: Commentsmentioning
confidence: 80%
“…Furthermore, clinical over-staging may also lead to a reduced chance of cure in a number of patients, in which the diagnosis of T4 was made in error. Our previous studies 29) as well as recent reports 30) have shown that the metabolic response of esophageal cancers to preoperative CRT as assessed by FDG-PET more accurately reflects tumor regression and predicts prognosis, compared with that by conventional imaging including CT. Therefore, accurate initial staging and response evaluation by using multimodal diagnostic tools including FDG-PET is no doubt necessary to provide appropriate treatments and also to improve prognosis of esophageal cancer patients with T4 tumors.…”
Section: Commentsmentioning
confidence: 80%
“…In our institute, EUS is routinely performed for staging of superficial oesophageal cancers, but not for deeply invading (T3-T4) oesophageal cancers because the fiberscope often could not pass through the latter tumours due to stenosis. From March 2000, we have used FDG-PET for the clinical staging of locally advanced oesophageal cancers and for evaluating the patient response to neoadjuvant treatment (22)(23)(24). FDG-PET reportedly achieves higher specificity and comparable sensitivity for assessing regional and distant LN involvement, compared with CT and EUS (21,43,44).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Spherical LNs >1.0 cm in maximum transverse diameter were diagnosed as metastasis-positive on CT scans (13,20,21). LNs that were visible but <1.0 cm on the long axis by CT scan were regarded as metastasis-positive if focal prominent 18-FDG uptake was significant on the PET scan, compared with normal mediastinal activity (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…10% to 80%) and typically has been chosen tailored to a retrospective data set rather than prospectively evaluated [8,[10][11][12][13][14] . In other studies, persistent uptake within the primary tumor site on a single post-treatment PET correlated with residual viable tumor and poor survival [9,[15][16][17] . However, the specific SUVmax value used in these series as a cutoff varied from 2.5 to 4.0, and unfortunately other recent studies similarly designed have concluded that a single post-therapy PET scan is not adequate in determining response within the primary tumor [18][19][20] .…”
Section: Pet Utility In Treatment Responsementioning
confidence: 76%
“…Patients with persistent disease after neoadjuvant therapy and prior to surgery have a poorer outcome and may best be managed without surgery [8,9] . A PET scan may be helpful in more accurately determining patient response to treatment to facilitate choosing appropriate additional therapy.…”
Section: Pet Utility In Treatment Responsementioning
confidence: 99%